(untitled) (Educação e Pesquisa, 2015)
The main subject of this interview is literacy in the digital age, considering migration in the globalized world. Digital culture and its differences in relation to print culture constitute new possibilities of experiencing space and time, which consequently produces new ways of interaction between subjects around the uses of writing. The uses of writing and literacy practices are thus developed in contexts whose limits and boundaries are redefined by the empowerment resulting from the appropriation of the devices of literacy world by those who participate in such contexts. Technical resources allow informing through distances, contrasting different perspectives, rescaling the knowledge (about themselves) when faced with the other, the foreign. They enable the immigrant to compose strategies of permanency in the destination country, and provide those who stayed in their home country with resources for the development of new literacy practices.